Visual Luminescent Probes Constructed by Eu3+ Complex-Functionalized Silica Nanocomposites and Their Langmuir-Blodgett Films at Interfaces - Ma, Yue-Yang (Langmuir : the ACS journal of surfaces and colloids, 2020)
The trivalent europium ion (Eu3+) has garnered a great deal of interest for the design of luminescent materials possessing compound-independent emission bands, strong luminescent intensity, and long emission lifetimes. We herein introduce a synthetic methodology capable of constructing visual luminescent probes from Eu3+ complex-functionalized silica nanocomposites and their Langmuir-Blodgett (LB) films at interfaces. In order to facilitate the coordinative stabilization of Eu3+ over carrier surfaces, silica nanoparticles (nanoSiO2) were pregrafted with terpyridyl (TPy) to make nanoSiO2TPy linkers. Then, a well-designed coordination reaction of nanoSiO2TPy with EuCl3 and 2,6-pyridinedicarboxylic acid (DPA) was carried out at solid-liquid and air-water interfaces, where our desired material (denoted as nanoSiO2TPyEuDPA) and its corresponding LB film are obtained. The presence of TPy and DPA interacting with Eu3+ plays a key role in regulating the chemical nature of the particle surface, hence giving rise to closely packed nanocomposite arrays in the film. As a result, the improvement in uniformity and stability is achieved alongside the enhancement in emission intensity and lifetime. With such advantageous optical properties, we find them workable as facile, green, and affordable luminescent sensors, by which a range of common toxic anions (Cr2O72-, MnO4-, and PO43-) can be visually and quantitatively recognized. Notably, the LB film-based material could afford a higher Ksv value (1.53 × 105 M-1), a lower detection limit (0.157 μM), and better recyclability than its original powder analogue, showcasing its utility as a more promising candidate for practical use